Acute Coronary Syndrome: Approach and impacts - Neves, Luana Tavares; Geraldi, Luiz Osvaldo Becker; Correia , Alissa Paglioco; Kleiner, Ana Clara Haluch Maoski; Damaceno, Gabriela Alves Miranda; Bassi, Thomaz Nassif Jorge; dos Santos, Luiz Henrique Gonçalves; de Ávila, Lucas Mendonça Silva; Kretschmer, Anderson; Nieto, Walter Rocha Passos; dos Santos, Julia Pina Vieira; Fernandes, Larissa Guerra (Seven Editora, 2024)
Chest pain is one of the most frequent reasons for seeking emergency care. Among the causes of this pain, acute coronary syndrome comprises one of the main pathologies. Such a syndrome is serious, and must be correctly diagnosed, in order to carry out the correct management of the patient, avoiding irreducible consequences. The objective of this study is to provide the necessary support for the understanding of this syndrome as a whole. For this, a narrative literature review was carried out, with the delimitation of articles published in the last 5 years, from 2019 to 2024, in the Index Scielo and Pubmed bibliographic databases. Articles that did not meet the criteria established in the methodology were discarded, resulting in a total of 25 selected articles. After careful analysis, the information collected served as a basis for the construction of the review. It was observed that the syndrome is extremely important, especially in the scenario of emergency medicine and emergency care. Thus, it is necessary that physicians be properly trained on the subject, in order to avoid unfavorable outcomes for patients, and iatrogenesis. DOI:https://doi.org/10.56238/sevened2024.016-016